Dampak Penggunaan Aplikasi Tiktok Terhadap Minat dan Prestasi Belajar PAI - Refo, Afrizal (LPPPI Publishing, 2021)
This study aims to determine how the positive and negative impacts of using the Tiktok application on interest and achievement in PAI learning on students at SMAN 1 Langsa and to find out how to increase interest and achievement in PAI learning on students at SMAN 1 Langsa. Interest in learning, especially in PAI subjects, is very important. If children experience dependence on the Tiktok application, this will affect interest in learning so that it reduces study time and student achievement will decrease because the concentration of learning in children is reduced. In using the Tiktok application, it is also not good if done continuously. If done continuously, it will result in someone being addicted to using the Tiktok application, so that interest and learning achievement in students decreases. This research is a type of descriptive research using a qualitative approach. Data collection uses observation, interview, and documentation methods. While data analysis uses data reduction, data presentation, and conclusion drawing. The results showed that between the positive impact and the negative impact of using the Tiktok application, there were more negative impacts, the positive impact was only to fill students' boredom and the negative impact resulted in students not concentrating on learning, lack of interest in learning religion, and students' learning achievement decreased, students use their cellphones more to use the Tiktok application every day for at least 4 hours each time using the application so that students do not read books, do not do the homework given by the teacher and the teacher explains the lesson students are sleepy because they stay up late using the Tiktok application until late at night.